Cognitive Behavioral Therapy Improves Physical Function and Fatigue in Mild and Moderate Chronic Fatigue Syndrome: A Consecutive Randomized Controlled Trial of Standard and Short Interventions - Gotaas, Merethe Eide; Stiles, Tore C.; Bjørngaard, Johan Håkon; Borchgrevink, Petter C.; Fors, Egil A. (Frontiers in Psychiatry, 2021)
Objective: To study whether standard cognitive behavioural therapy (CBT) and a shorter, interpersonal oriented cognitive behavioural therapy (I-CBT) can improve physical function and fatigue in patients diagnosed with mild to moderate chronic fatigue syndrome (CFS) in a multidisciplinary fatigue clinic. Design: Consecutively 236 participants 18 to 62 years old meeting the Centre of Decease Control, CDC 1994 criteria, with a subsample also fulfilling the Canadian criteria for CFS, were randomly allocated to one of three groups. Two intervention groups received either 16 weeks of standard CBT or 8 weeks of I-CBT versus a waiting-list control group (WLC). Primary outcome was the subscale Physical Function (PF) from SF-36 (0-100). Secondary outcome was amongst others fatigue measured by Chalder Fatigue Questionnaire (CFQ) (0-33). Outcomes were repeatedly measured up to 52 weeks from baseline. Results: The additional effect relative to baseline at post-intervention for SF-36 physical function was 14.2 (95% CI 7.9 to 20.4 p<0.001) points higher for standard CBT and 6.8 (0.5 to 13.2 p=0.036) points higher for I-CBT compared with the control group. The additional effect relative to baseline at post-intervention for fatigue was 5.9 (95% CI 0.5 to 10.5 p=0.03) points lower for standard CBT compared with the control group but did not differ substantially for I-CBT 4.8 (95% CI -0.4 to 9.9 p=0.07). The positive change in physical function persisted at one-year follow-up for both treatment groups, and for standard CBT also in fatigue. The two intervention groups did not differ significantly in self-reported physical function and fatigue at the one-year follow-up. No serious adverse reactions were recorded in any of the groups during the trial period. Interpretation: A 16-week standard, individual CBT intervention improves physical function and fatigue in CFS outpatients with mild to moderate disease. A shorter eight-week I-CBT program improves physical function. Both treatments are safe, and the effect persist one year after baseline.